If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(2x + 3) = 9(x + -1) Reorder the terms: 7x + -1(3 + 2x) = 9(x + -1) 7x + (3 * -1 + 2x * -1) = 9(x + -1) 7x + (-3 + -2x) = 9(x + -1) Reorder the terms: -3 + 7x + -2x = 9(x + -1) Combine like terms: 7x + -2x = 5x -3 + 5x = 9(x + -1) Reorder the terms: -3 + 5x = 9(-1 + x) -3 + 5x = (-1 * 9 + x * 9) -3 + 5x = (-9 + 9x) Solving -3 + 5x = -9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 5x + -9x = -9 + 9x + -9x Combine like terms: 5x + -9x = -4x -3 + -4x = -9 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -4x = -9 + 0 -3 + -4x = -9 Add '3' to each side of the equation. -3 + 3 + -4x = -9 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = -9 + 3 -4x = -9 + 3 Combine like terms: -9 + 3 = -6 -4x = -6 Divide each side by '-4'. x = 1.5 Simplifying x = 1.5
| Xa+15=x*4 | | 3x+1=4x+8 | | x+8x=3+x | | Y+y+15=23 | | 15/10x4= | | y=-1X+20 | | f(1)=5x^2+100 | | -.2(1-x)=4(4+.1x) | | f(x)=5x^2+100 | | 28078.82+0.9010x+17491.84+0.8746x+8489.33=0.9563x+19126.34+26237.77+0.8489x+8489.33 | | X/22=4/11 | | 0=r+10 | | 8.13=x | | -7x+6y=-24 | | -7x+6x=-24 | | 3(5x-1)=50 | | -2=0.666x-x | | 48x+20y=6 | | ln(9)+ln(x-10)=3 | | -10r^2-3r+12= | | 69x^2+27=0 | | 4x+6y=124 | | 5x+3y+6z=42 | | y=0.05(x-30)+6 | | 0.2x+6=1.2x | | y=0.05(x-30)2+6 | | 6x+2y+4z=36 | | 2^3(x-3/4)-12=2 | | -10v^2-4p^2+5h^2= | | 5p-3(p-5)+4(q-5)= | | 3(2a-8)=4(7+a) | | 2x+4y+2z=30 |